Sub-acute toxicity evaluation of Ziziphus spina-christi and Adenanthera pavonina leaf extracts combination in rats: an in vivo study - Ngibad, Khoirul; Ayu , Patricia Gaby; Fafa , Angelica Rosia; Tria , Novitasari; Farichatul , Wachda (Universitas Muhammadiyah Purwokerto, 2025)
Background: The safety of combined herbal extracts remains underexplored, particularly for Ziziphus spina-christi and Adenanthera pavonina, which contain bioactive compounds with potential toxic effects. Objective: To evaluate the sub-acute toxicity of combined leaf extracts on hematological, biochemical, and organ morphology parameters in Wistar rats. Method: Thirty male and female rats were randomized into five groups receiving vehicle control or extract doses of 4000, 8000, and 10,000 mg/kg BW for 21 days following OECD 407. Blood hematology, renal biomarkers, bilirubin levels, organ weight, and morphology were analyzed. Results: Mortality increased dose-dependently, reaching 20% in males and 10% in females at 10,000 mg/kg BW. Hematology and renal biomarkers showed no significant differences (p>0.05). Total bilirubin increased at the highest dose. Morphological abnormalities, including pale discoloration and dark foci, were observed in liver and kidneys at higher doses. Conclusion: The combination extract is safe up to 8000 mg/kg BW, while 10,000 mg/kg BW induces organ alterations and increased mortality.